HALF: Human-Assisted Labeling Feedback Method for Subject Mining - Santos, Bruno Rogério S. dos; Rocha, Leonardo Sampaio; Menezes, Vinícius de M.; Costa Júnior, Evilásio; Lessa, Pedro Henrique L. (Anais do Latin American Symposium on Digital Government (LASDiGov), 2025)
The increasing volume of unstructured texts in Official Gazettes highlights the need for robust semantic search engines. To address this, we propose a hybrid approach combining machine learning, human supervision, and a Large Language Model (LLM). The HALF (Human-Assisted Labeling Feedback) method, leveraging GPT-4o Mini, classified subjects in publications from the Official Gazette of Ceará. It assigned subjects to 1.044 publications with 0.8889 accuracy compared to ground truth. This approach enhances semantic search, improves retrieval and decision-making, and extends to other legal domains. Moreover, it offers a scalable solution, outperforming traditional unsupervised methods in accuracy and relevance.